Komunikasi Krisis Sebagai Upaya Penanganan Pandemi Covid-19 Tahun 2020 di Kota Semarang - Hanifa Maylasari; Wijayanto Wijayanto; Laila Kholid Alfirdaus (Mahesa Research Center, 2022)
The enactment of Restrictions on Community Activities applied in the city of Semarang runs with a tug-of-war system, because it considers economic factors. This research was conducted to uncover the crisis communication system of the Semarang City Government during the covid-19 pandemic. Qualitative approach becomes a tool of researchers in obtaining information. The research method conducted is digital ethnography based on tracking information data through social media owned by the Semarang City Government and local media in the Semarang City Government area, as well as in-depth interviews with stakeholders. Data analysis techniques in this study through data reduction, data display and draw conclusions. The results showed that the crisis communication applied in the Semarang City Government was running inconsistently, this happened because of concerns about economic conditions. Crisis communication is carried out centralistically vertically, depending on the direction of the central government. The slow process of communication to the community is overcome by policies made based on statistics on the number of victims of the covid-19 pandemic. If the victims of covid-19 increase then the policy of Implementing Restrictions on Community Activities will be tightened, while if the victims of covid-19 begin to decrease then the policy of the Community Activity Restriction Regulation is loosened. In addition, the aspirations of the community in the process of making policies in dealing with the covid-19 pandemic are represented by a group and have not been thorough. Thus, the communication of the crisis of the Semarang City Government to the community goes one way.